IMPLEMENTATION OF AQUATOX, PAMOLARE AND WASP MODELS TO MOGAN LAKE - Karaaslan, Yakup; Erturk, Ferruh; Akkoyunlu, Atilla (YILDIZ TECHNICAL UNIV, 2010)
In this study, the effects of Physical and chemical parameters to Mogan Lake have been investigated. In this study, AQUATOX, WASP and sub-models of PAMOLARE have been used. The reason for the preference of Mogan Lake is the abundance of historical date in chemical, biological, physical and hydrological aspects. Parameters for the four selected stations at Mogan Lake were measured by the Environmental Reference Laboratory throughout the year 2002 on a monthly basis. Besides, chemical and physical data for all the creeks discharging into Mogan Lake were also measured by the Environmental Reference Laboratory for the same year on a monthly basis. All these data has been used as input parameters for Aquatox, Wasp and Pamolare Models. The simulation results of Pamolare, Wasp and Aqautox Models were compared in this study. 1-Layer, 2-layer and structurally dynamic sub-models of Pamolare 3 and Pamolare 2, which is Structurally Dynamic Model for shallow lakes, have been tested for the first time. Two-year simulations have been performed for TN, TP, Chlorophyll a and Zooplankton parameters by using Pamolare 3 and in addition to those parameters for Phytoplankton, Organic Substances and Nitrogen and phosphorus in sediment by using Pamolare 2. The simulation results have been compared with actual measured data of Mogan Lake for the years 2004 and 2005 and found to be highly incompatible. One-year simulations of Suspended Solids, Dissolved Oxygen, Chlorophyll a, Total Nitrogen and Total Phosphorus have been made by using Water Quality Analyses Simulation Program (WASP). When those results were compared with the actual data in Mogan Lake, TN and TP are partly compatible and the other parameters are not compatible. During the comparison of the Water Quality Models, good simulation results have been obtained particularly for Suspended Solids, pH and Temperature in the studies in which Aquatox Model is used. Moreover, the values obtained for Total Nitrogen and Dissolved Oxygen are considerably close to the actual values. A continuous increasing tendency has been observed for the simulation of total phosphorus parameter as in the WASP model.
Keywords: Water quality model; simulation; calibration; Engineering